2015
DOI: 10.26719/2015.21.4.280
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of meglumine antimoniate against L. tropica in a recently emerged focus of cutaneous leishmaniasis in Birjand, eastern Islamic Republic of Iran

Abstract: With limited options to treat cutaneous leishmaniasis, constant monitoring of the rate of resistance to pentavalent antimony-based drugs is needed. This study identified the infecting Leishmania species and evaluated the results of meglumine antimoniate (Glucantime®) therapy in a new focus of cutaneous leishmaniasis in Birjand, eastern Islamic Republic of Iran. Smears from 150 patients showed that 141 patients were infected by L. tropica and 9 by L. major. In total, 141 patients with L. tropica infection compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 19 publications
0
6
1
Order By: Relevance
“…The IV SSG failure rate in the current study was 29.8%, which was higher than that reported in previous studies on the antimoniate treatment of L. tropica CL (15). The failure rate among patients who received meglumine antimoniate (Glucantime) intramuscular injections (20 mg/kg for 20 days) in Iran was 9.8-12% (20,21). This may suggest that the L. tropica species in Israel are more resistant compared with those in other parts of the world, including the Middle East.…”
Section: Characteristicscontrasting
confidence: 59%
“…The IV SSG failure rate in the current study was 29.8%, which was higher than that reported in previous studies on the antimoniate treatment of L. tropica CL (15). The failure rate among patients who received meglumine antimoniate (Glucantime) intramuscular injections (20 mg/kg for 20 days) in Iran was 9.8-12% (20,21). This may suggest that the L. tropica species in Israel are more resistant compared with those in other parts of the world, including the Middle East.…”
Section: Characteristicscontrasting
confidence: 59%
“…Karamian et al (49) reported an emerging focus of ACL in Birjand county in South Khorasan province where L. tropica was identified in 89% (n = 51/57) of urban cases and 91% (n = 21/23) of ACL patients were rural dwellers. L. major was also detected in both urban and rural regions.…”
Section: Eastern Iranmentioning
confidence: 99%
“…For primary sores, topical or systemic treatment approaches such as chemicals and freezing are used (Ejov and Dagne, 2014). Meglumine antimoniate (Aflatoonian et al, 2019;Karamian et al, 2015;World Health Organization, 2014) is the conventional treatment for CL. Individuals are usually resistant to reinfection from the same species after healing, and a lifelong immunity will often be produced.…”
Section: Discussionmentioning
confidence: 99%